Second phase Chiba study of mother and child health (C-MACH): Japanese birth cohort study with multiomics analyses - Chisato Mori; Masahiro Watanabe; Akifumi Eguchi; Akira Hata; Masaya Koshizaka; Kenichi Sakurai; Midori Yamamoto; Hideoki Fukuoka; Naoki Shimojo; Masamichi Hanazato; Norimichi Suzuki; Akiko Kawanami; et al. (BMJ Open)
Purpose Epidemiological studies have reported that environmental factors from fetal period to early childhood can influence the risk of non-communicable diseases in adulthood. This concept has been termed the developmental origins of health and disease (DOHaD). The Chiba study of Mother and Child Health (C-MACH) is a DOHaD concept-based birth cohort study which started in 2014. This study aims to investigate the effects of genetic and environmental factors, particularly fetal and postnatal living environment, on children’s health. We also aim to identify candidate biomarkers for their health status. Moreover, the second phase study of C-MACH which was initiated in 2021 aimed at expanding the sample size, especially for gut microbiota and epigenomic analysis; it also aimed at clarifying the impact of the coronavirus disease 2019 (COVID-19) pandemic on children’s health.Participants This study consists of four hospital-based cohorts. Women who were <13 weeks pregnant and their partners were enrolled in the study. All data and biological samples will be stored in the Chiba University Centre for Preventive Medical Sciences.Findings to date A total of 561 women and their partners provided their consent to participate in this study. Of these women, 505 completed the questionnaire during the early gestational period. The mean age of the 505 women at enrolment was 33.0 (SD, 4.5) years. The mean prepregnancy body mass index (BMI) was 21.7 (SD, 3.6) kg/m2, with 74.5% of the women having a BMI of 18.5–24.9 kg/m2. About 5.2% of the women smoked cigarettes during the early stages of pregnancy.Future plans The primary study outcomes are allergies, obesity, endocrine and metabolic disorders and developmental difficulties in children. Variables related to genome, metabolome, epigenome, gut microbiota and exposome will be evaluated as health-related factors. The relationships between these outcomes and the health-related factors will be analysed.